Bentonite-based composites with ceramic and metallic powders additions for use as filters - Matei, Simona Corina; Stoicănescu, Maria; Bela, Varga; Tiron, Elena Lăcrămioara; Crișan, Aurel (SAGE Publications, 2021)
This paper represents the study of bentonite matrix composite reinforced with ceramic (Al2O3 and SiC) and metallic (Al and Fe) particles for the production of filters. Ceramic powders were used to generate pores and metallic particles to control the pore size (to finish them). These materials were added to composites in two stages. In the first stage, the ceramic particles (Al2O3 and SiC) were added to the bentonite matrix, thus obtaining two types of composites. In the second stage, for each type of composite, metallic powders of Al and Fe were added. The composites was prepared by mixing the components, cold pressing for compaction in cylindrical samples and, at the end, sintering at 1250 degrees C. The samples thus produced underwent studies by optical and electron microscopy, diffractometry, dilatometry and thermal analysis and tests to determine the compressive strength and the porosity. Thus, there was obtained useful information regarding the behaviour and impact of the reinforcing materials in the process of producing the composites, and on their impact on the final properties of the composites produced.
Keywords: ceramic filters; metallic particles; thermal analysis; bentonite; Ceramic composites